2019
DOI: 10.5114/hivar.2019.84198
|View full text |Cite
|
Sign up to set email alerts
|

Markers of liver fibrosis and apoptosis in patients with HIV mono-infection and HIV/HCV co-infection

Abstract: Introduction: Human immunodeficiency virus (HIV)/hepatits C virus (HCV) co-infection has a significant impact on liver-related morbidity and mortality. Among many other pathogenic mechanisms leading to accelerated hepatic disease are liver fibrosis and hepatocyte apoptosis. Hence the objective of this investigator-initiated cross-sectional study was to analyse the plasma levels of hyaluronic acid, cytokeratin-18, and cytochrome c in order to assess their impact on progression of liver disease in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Correlation between CK18 and HA confirms the theoretical relationship between hepatocyte apoptosis and liver fibrosis, described by Canbay et al (2004), Guicciardi and Gores (2005) and Friedman (2010). A clinical study (Vîksna et al, 2019) also indicated that HIV/HCV co-infection impacts CK18 indirectly through the level of HA.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Correlation between CK18 and HA confirms the theoretical relationship between hepatocyte apoptosis and liver fibrosis, described by Canbay et al (2004), Guicciardi and Gores (2005) and Friedman (2010). A clinical study (Vîksna et al, 2019) also indicated that HIV/HCV co-infection impacts CK18 indirectly through the level of HA.…”
Section: Discussionsupporting
confidence: 79%
“…At the same time, there was no association between CK18 and other markers of liver fibrosis in this group. Higher levels of CK18 in HIV/HCV patients than in HIV mono-infected patients have been shown previously in two studies in Latvian cohorts (Vîksna et al, 2019;Madelâne et al, 2019). Our study merges data from both Latvian studies and provides CK18 levels in a relatively large group of HIV/HCV coinfected and HIV mono-infected patients, and the association of CK18 levels with other non-invasive markers of liver fibrosis, and describes CK18 dynamics in a fourmonth-long period.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In a preclinical model of HIV, the dual-reconstituted humanized mouse, HIV infection resulted in hepatocyte dysfunction and death with reduction of albumin levels [13]. Clinically, HIV was found to exacerbate hepatocyte apoptosis in patients with HBV and HCV infection with higher number of hepatocytes expressing the death receptor Fas in co-infected patients [32][33][34]. In our PWH, transaminases decreased significantly after initiation of ART, even though their pre-ART levels were not too high to begin with and albumin levels increased, positively correlating with increasing FDG uptake.…”
Section: Discussionmentioning
confidence: 99%
“…There is clinical evidence of the importance of hepatocyte apoptosis in the development of liver disease in HIV patients. In this sense, a recent study has shown the correlation between high plasma levels of hyaluronic acid, a relevant liver fibrosis marker, and caspase-cleaved CK-18 in patients with HIV/HCV co-infection [ 40 ]. Similarly, biopsies from HCV/HIV co-infected patients show that higher number of hepatocytes express the death receptor Fas (CD95, a member of a subgroup of the tumor necrosis factor (TNF) receptor superfamily) and undergo irreversible apoptosis compared to biopsies from HCV-infected patients [ 41 ].…”
Section: Introductionmentioning
confidence: 99%